GESTÃO DA INOVAÇÃO EM SERVIÇOS DE ESTÉTICA E EMAGRECIMENTO: ESTUDO DE UMA EMPRESA NO MUNICÍPIO DE GUARAPUAVA-PR - MORENO, LUCILÉIA GALDINO (2022)
The service sector is the largest branch of Brazil's economy and the largest generator of jobs in the country. In this sector, one of the fastest growing economic activities in recent years is CNAE 9602502, which refers to aesthetic activities and other beauty care services. In this expanding and progressively more competitive market, and also with increasingly demanding customers, it is essential that entrepreneurs develop their services with excellence to generate a competitive edge. Both in academia and in business, innovation has been recognized as of great importance to improve competitiveness. As a result of conceptual advances and the imperative of innovation, there has been continuous adoption and diffusion of innovation management practices by companies. Innovation management comprises the structuring and management of a set of routines whose objective is innovation, that is, transforming ideas into new or significantly improved products and commercialized by companies. This situation motivated the present study, which has as its general objective: to analyze how a company of aesthetic and slimming services has articulated its internal context and its processes to manage innovation. The study developed has a descriptive character and a qualitative approach, adopting the case study method and using an in-depth individual interview for data collection based on a semi-structured script with the company's managers. To understand the speeches, they were analyzed and interpreted by applying the content analysis technique from three categories of analysis: a) dimensions of service innovation; b) dynamic capabilities for managing service innovation; c) operational resources and capabilities for service innovation. The results showed that the dimensions of service innovation, individually or in combination, led to new service functions for the company and resulted in incremental innovations, in innovation patterns: innovation with supplier support, innovation within services and customer innovation. It was found that to create and carry out innovations, the researched company uses dynamic capabilities and operational resources and capabilities related to the domain of functional management and which are inserted in its own routines and processes. Thus, in the researched company, service innovation took several forms and is linked to different parts of the value creation process of that company. As a practical contribution, this study enables new knowledge and a better understanding of the management of service innovation, being able to help those involved in the management of service innovation in their activities.